Effect Of Arbuscular Mycorrhizal Fungi And Cytokinins On Growth And Yield Of Sorghum Plants (Sorghum bicolor (L.) Moench) - Hidayat, Ikhsan Syarif; Robani, Imam Fathu; Dukat, Dukat (Ann Publisher, 2025)
Sorghum has many advantages, including high adaptability, drought resistance, high productivity, and resistance to pests and diseases. This makes sorghum a potential cereal crop to be developed on marginal land. Efforts to increase the growth and yield of sorghum plants include the use of biological fertilizers based on arbuscular mycorrhizal fungi (FMA) and adding cytokinin hormones. FMA can increase nutrient uptake and increase plant resistance to drought, while cytokinin hormones can increase cell division and growth. This research was conducted in June-September 2024 in Pancalang Village, Pancalang District, Kuningan, West Java. The research method used was experimental method, with randomized group design (RAK), 16 treatment combinations of FMA dose and Cytokinin concentration and repeated twice. Variables observed included root length and volume, flowering age, sap volume, Brix content, panicle length, fresh weight, testing was done through analysis of variance and Scott-Knott cluster test. The results showed that the combination of FMA dose treatment and Cytokinin concentration gave a significant effect on all variables. High weight per plot results were obtained in the application of FMA doses of 15, 30 and 45 g/plant combined with cytokinin concentration of 15 ppm which amounted to 1,148.00 grams, 1,118.00 grams and 1,090.00 grams, respectively.